Etiology and Pathogenesis of Congenital Cardiac Diseases in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article describes the concepts of congenital heart defects, their etiology and pathogenesis, the processes occurring in the cardiovascular system during a number of pathologies, and treatment options. Conclusions and findings are provided on the topic and the material studied.